ANALISIS VARIASI WAKTU DELIGNIFIKASI DAN KONSENTRASI DEKSTRIN TERHADAP PEMBUATAN KERTAS TISU SERBET DARI LIMBAH TONGKOL JAGUNG - Raiqa Biyan Sukmawijaya; Vika Rizkia; Emmidia Djonaedi (INKOFAR, 2025)
This study explores the potential of corn cobs as an alternative raw material for environmentally friendly tissue paper production. Corn cobs are rich in cellulose but contain lignin, which must be removed through a delignification process. In this research, soda delignification was applied with varied durations (30, 60, and 90 minutes), combined with the use of dextrin as a binding agent at concentrations of 5%, 10%, and 15%. The resulting tissue paper was evaluated based on Indonesian National Standards (SNI), focusing on tensile strength, water absorbency, sheet integrity, and grammage. The results showed that a delignification time of 60–90 minutes combined with 10–15% dextrin produced the best quality tissue paper. The sample treated for 60 minutes with 15% dextrin exhibited the highest tensile strength (400 N/m), while the sample treated for 90 minutes with 5% dextrin achieved the highest water absorbency (114 mm/10 minutes). These findings indicate that corn cob waste holds significant potential as a sustainable raw material for tissue paper production, supporting green manufacturing principles and agricultural waste valorization.